Reasons for resubmission of research projects to the research ethics committee of a University Hospital in São Paulo, Brazil - Bueno, Mariana (2009)
INTRODUCTION: It is important to know the reasons for resubmitting research projects to the Research Ethics Committee in order to help researchers to prepare their research projects, informed consent forms and needed research documentation. OBJECTIVES: To verify the reasons for resubmitting projects that were previously rejected by the Ethics Committee. METHOD: This is a cross-sectional study that evaluated research projects involving human beings. Research projects were submitted in 2007 to the Research Ethics Committee of the Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. RESULTS: One thousand two hundred and fifty six research projects were submitted to the ethics committee and the average time for evaluating the research projects and related documents until a final decision was reached was 49.95 days. From the total, 399 projects were reviewed in 2 or more meetings until a final decision was reached. Of these, 392 research projects were included in the study; 35 projects were subsequently excluded for involving animals. Among the research projects included, 42.5% concerned research with new drugs, vaccines and diagnostic tests, 48.5% consisted of undergraduate students' research projects, 68.9% of the research had no sponsorship, and 97.5% were eventually approved. The main reasons for returning the projects to the researchers were the use of inadequate language and/or difficulty of understanding the informed consent form (32.2%), lack of information about the protocol at the informed consent form (25.8%), as well as doubts regarding methodological and statistical issues of the protocol (77.1%). Other reasons for returning the research projects involved lack of, inaccuracy on or incomplete documentation, need of clarification or approval for participation of external entities on the research, lack of information on financial support. CONCLUSION: Among the research projects that were returned to the researchers for additional clarification, the main reasons were inadequacies or doubts about the terms used in the informed consent form as well as lack of information regarding the research at the informed consent form and methodological and statistical issues regarding the protocol.